A Homobivalent SPECT Radioligand - Serinol Appended Methoxyphenyl Piperazine Derivative for Serotonin Receptor Imaging** - Rangaswamy S.; Saklani M.; Kumar R.; Mathur R.; Kaul A.; Tiwari A.K.; Kaur-Ghuman S.; Mishra A.K.; Varshney R. (My University, 2025)
Serotonin receptor subtypes are predominantly accountable for various neurophysiologic and cognitive processes and are expressed in the hippocampus region. SPECT based radioligands offer a cost effective understanding to the molecular changes which are used in the diagnoses of various neurological disorders. A Homobivalent approach was used to synthesize 1-(2-methoxyphenyl) piperazine based ligand by using click chemistry to incorporate two moieties of MPP via a linker (serinol) for SPECT (Single Photon Emission Computerised Tomography) evaluation. Molecular docking studies show better affinity for radiolabeled DO3 A-serinol-bis-MPP complex. The radiolabeling efficiency of conjugate was optimized and evaluated for stability by various parameters and was found to be 99 %. The complex shows appreciable brain uptake in rabbit. Ex Vivo pharmacology indicated approximately 50 % of the total brain uptake in the hippocampus region which showed the selective preference of the ligand for serotonin receptor. This study could be considered as a novel, informative and preclinical finding for using the synthesised 99mTc-DO3 A-serinol-bis-MPP ligand to target serotonin receptor by SPECT imaging. © 2021 Wiley-VCH GmbH